PERAN BAITUL MAAL WAT TAMWIL (BMT) DALAM MENUMBUHKAN EKONOMI SYARIAH (Studi di BMT Surya Abadi Jenanngan Ponorogo) - Khabibi, Romadhon Khabibi; Rois, Adib Khusnul; Iman, Nurul; Apriliana, Yuka Maulinda (JSE: Jurnal Sharia Economica, 2025)
BMT Surya Abadi Jenangan is a sharia financial institution or cooperative-based Islamic economic institution located in Jenangan, Ponorogo, which prioritizes the principles of people's economy and Muhammadiyah ideology, this BMT aims to improve people's welfare through the development of sharia economy in the community. The results of the study show that BMT Surya Abadi Jenangan has succeeded in carrying out its objectives in growing the sharia economy as follows: 1). Sales of sharia BMT products, 2). Facilitating the provision of financing to entrepreneurs, 3). Types of financing using sharia contracts.